Знаки часу у вченні Папи Івана ХХІІІ - Волинець, Оксана (Lviv Politechnic Publіshing House, 2016)
Проаналізовано позицію Римського понтифіка Івана ХХІІІ у розпізнаванні і прочитанні “знаків часу” як світових подій та явищ, які становлять загрозу світовій безпеці і мирному співіснуванню міжнародної спільноти. У контексті відповіді на знаки часу, застосовуючи аналітичний, структурно-функціональний, системний методи та контент-аналіз, досліджуються, подані у працях Івана ХХІІІ рекомендації та механізми врегулювання міжнародних конфліктів та забезпечення миру і міжнародної безпеки. The article analyzes encyclicals of Pope of Rome John XXIII, which are dedicated to the issue of threats to international security and global peace. John XXIII investigated treatment of the concept of “signs of timе” and their interpretation in terms of the ColdWar and the Caribbean crisis. The main provisions of letters and encyclicals of John XXIII are analyzed, applying analytical, systematic, structural and functional methods and content analysis. As a result, their significant contribution to peace and security is revealed. The Pope provides characteric view on scientific and technological progress of mankind in all its positive and negative aspects, such as arms race, emergence of modern weapons of mass destruction, division of the world into parties and blocks, etc. Those characteristics were treated as unique signs of the time which requires immediate and adequate solution for the whole universal community, international organizations, each state itself, and the Church. Thus, the Pope John XXIII interprets all these negative trends of the modern world as amoral problemwhich destroys balance between politics andmorality. Further on, we investigate position of the Pope John XXIII concerning the need for renewal of the Church and its missionary activities in the context of social and political development. The Second Vatican Council, its Declarations, decrees and constitutions became the result of Pope’s aspirations. Those achievements have opened new opportunities for the Church within new social and political conditions of human society development. Special attention is given to the analysis of John XXIII’s encyclical “Peace on Earth”. It proposes methods, ways, and mechanisms to overcome international conflicts and rebuild the global security system. It is alleged that Pope John XXIII’s recommendations are still relevant today and international community can use them to achieve peace, universal order and ensure global security.
Signs of time in teachings by Pope John XXIII
Keywords: “знаки часу”; мир; безпека; конфлікт; Церква; signs of time; peace; security; conflict; the Church